The Welfare of Animals The Silent Majority - Phillips, Clive (Animal Welfare, 2009)
The quality of life that we provide for animals for food, companionship, sport and clothing will determine their welfare, and even the welfare of wild animals is affected by human activities. This book challenges us to reflect on that silent majority of animals with no voice. We are increasingly questioning whether our use of animals is necessary, desirable and humane, The book provides a framework to make those difficult decisions. Aspects of welfare that are important to animals are considered, as well as their rights to different welfare standards. Provision for animal welfare depends as much on culture, gender and other societal influences as any scientific advances in management systems. The influence of intensification of animal use, especially in food production, on welfare is considerable and the international scale of welfare issues with different types of animals is discussed. The author describes his experiences investigating animal welfare in a vast range of different situations, from the Bedouins slaughtering sheep in the desert to livestock being transported from Australia to the Middle East. This book will be of interest to anyone concerned with the welfare of animals, but especially veterinarians, animal owners and animal scientists.